8.4k views
4 votes
Solve √(y-3)-√y = -3

1 Answer

3 votes

This equation has no solutions


Move the square root of y to the right hand sides:



√(y-3) = √(y)-3


To eliminate the roots, let's square both sides. But there is a crucial observation in this passage: you are allowed to deduce
a=b \implies a^2=b^2 only if both
a and
b are positive. Otherwise, you risk contraddictions like
2 = -2 \implies 4 = 4.


Since the left hand side is always positive when defined (it's a square root), we need to ask
√(y)-3 > 0 \iff √(y) > 3 \iff x>9. So, we're only accept answers if they're greater than nine.


Now we can square both sides:



y-3 = y- 6√(y) + 9


Simplify y's and bring 9 to left hand side:



-12 = -6√(y)


Divide both sides by -6:



2 = √(y) \implies y = 4


So, the solution is not acceptable. In fact, it would lead to




√(4-3) - √(4) = 1-2 \\eq -3





User Lyricat
by
5.9k points